#CHOOSETOCHALLENGE: COVID-19, COMMUNITY RESEARCH, AND THE CANAANITE WOMAN - M. Ibita; M.S. Ibita (Acta Theologica)
This study theologises on the Urban Poor Women and children with Academics for Reaching and Delivering on UNSDGs in the Philippines (UPWARD-UP) Project research team’s collaboration with the Alliance of Peoples’ Organisation Along the Manggahan Floodway (Alliance), Philippines. We posit that the theological process of seejudge-act, enhanced with evaluate-celebrate/ritualise, using feminist biblical characterisation in interpreting Matthew 15:21-28, serves as a spiritual resource for Christians working for the urban poor realisation of the United Nations’ Sustainable Development Goals during the COVID-19 pandemic and beyond. The Canaanite woman challenged Jesus’ identity and mission impacting on Christology and ecclesiology. This characterisation makes her a vital example and companion for the Alliance women leaders in achieving their prioritised SDGs (1 - No Poverty; 3 - Health and Well-being [in relation with the Environment]; 4 - Quality Education, and 16 - Justice, Peace and Strong Institutions seen from the lens of UNSDG 5 - Gender Equality) during the pandemic and beyond.